2020
DOI: 10.6007/ijarafms/v9-i4/6726
|View full text |Cite
|
Sign up to set email alerts
|

Financial System and Economic Development in Africa: A Review and Policy Recommendations

Abstract: This paper gears towards expounding the role, capacity, suitability, challenges and solutions for African financial systems in enhancing economic growth. This article employs a quasi-meta-analysis method of literature where an online search of materials related to the field of financial system and economic development were visited. Several journal publishers were included in finding the materials for this review. Search words and synonyms were used in the search processes, the reviewed papers were used in disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Activities involving the lending and borrowing of funds, investments, and offers of credit, stock trading, and insurance all provide the mechanism by which economic activities successfully take place. Kapaya [30] points out the three main roles of the financial system in the attainment of economic development in Africa: first, the facilitation of resource transfer across borders and time; second, the mobility of saving pools; and third, the competitive allocation of capital by investment. In surveying 22 emerging markets, Nguyen et al [31] also found that financial development has a positive effect on economic growth and that their relationship is linear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Activities involving the lending and borrowing of funds, investments, and offers of credit, stock trading, and insurance all provide the mechanism by which economic activities successfully take place. Kapaya [30] points out the three main roles of the financial system in the attainment of economic development in Africa: first, the facilitation of resource transfer across borders and time; second, the mobility of saving pools; and third, the competitive allocation of capital by investment. In surveying 22 emerging markets, Nguyen et al [31] also found that financial development has a positive effect on economic growth and that their relationship is linear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modernised financial systems greatly enhance the ability to efficiently allocate resources, mobilise funds, and provide access to credit for firms and individuals [12]. Investment and entrepreneurship are bolstered by stable financial systems, boosting output and creating more employment opportunities [13]. According to [14], banking and financial markets that are both stable and liquid are key to fostering capital accumulation and luring in FDI.…”
Section: Introductionmentioning
confidence: 99%